Application of Computational Fluid Dynamics (CFD) for the Evaluation of Fluid Convective Radial Heat Transfer Parameters in Packed Beds - Zambon, Mariana Teresa (2014)
A model to simulate the behavior of multitubular packed-bed catalytic reactors was recently proposed [Asensio, D. A.; Zambon, M. T.; Mazza, G. D.; Barreto, G. F. Ind. Eng. Chem. Res. 2014, 53, 3587−3605]. In particular, the model introduces a heat transfer coefficient hwf that accounts for an unmixed fluid film on the wall and a coefficient hf between the fluid channels at a distance Dp/2 from the wall. Computational fluid dynamics simulations intended to evaluate these parameters are described. Four regular sphere arrays between parallel planes that provide different combinations of wall and core channel voidages (ε1 and εc) were employed. Reynolds and Prandtl numbers ranges were 100 < Rep < 2000 and 0.4 < Pr < 3.5. Calculated values of hwf and hf are well correlated with those of ε1, εc, Rep, and Pr. Results for ε1 and εc values typical of randomly packed beds of low ratio Dt/Dp show good agreement with carefully analyzed data from the literature.